TEACHING LISTENING USING TOEIC APPLICATION - TUTI KARMIATI; yulyayu kurniawati (IKIP Siliwangi, 2018)
In a modern era many students like to learn english easily, many students learn english with listening something, like listening music in their mobile phone or in the radio, in this era we can find the western song in many place, like in the mall, radio, and so on. So we can hear the western song and learn listening english easily. Teaching listening is teaching students to learn to listen to languages and conversations using the ear. The reason for students being able to listen to spoken English is by letting them listen to variations and accents rather than just the teachers voice with its own idiosyncrasies. Listening is a very important skill in language learning and can’t be underestimated especially in an academic context and is separated in language so that listening has an important role in teaching the language including teaching English. The purpose of this study is to find out how English teacher use TOEIC applications in listening to students and how students respond to the use of TOEIC applications in student listening. Most students argue that the hardest is listening, and some of them even have difficulties in understanding the teachers who are teaching English. It states that students still have difficulty in listening and become one of the obstacles in learning English. The used of media as a tool or means in teaching and learning English that is very useful for students and teachers. This research is to know how big influence of TOEIC application media in learning to listen English. The design taken in this study is pre-experimental design and the author also uses quantitative research methods in conducting research. Subjects in this study were students of class XI AKP1 in SMKN 2 Karawang which amounted to 32 students as a sample. The author used a listening test to collect data. The procedure used in this research is pretest, treatment and posttest. Pretest was given to students to measure their knowledge before treatment, treatment is the researcher teach about TOEIC application, and posttest is a final result from the treatment.